2015
DOI: 10.1159/000375312
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Effects of Adaptive Servoventilation Therapy in Patients with Heart Failure and Cheyne-Stokes Respiration Compared to Healthy Volunteers

Abstract: Background: Nocturnaladaptive servoventilation (ASV) therapy is now frequently used to treat Cheyne-Stokes respiration (CSR), which is highly prevalent in patients with moderate-to-severe heart failure (HF) and characterized by periodical breathing (hyperventilation). Objectives: This study analyzed and compared the acute effects of a novel ASV device on carbon dioxide pressure (pCO2) and oxygen saturation (SaO2) in HF patients with CSR and healthy volunteers. The influence of being aslee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Twitch esophageal pressure (twPes) and twPgas were simultaneously recorded using balloon catheters (Cooper Surgical, Trumbull, CT, USA) transnasally inserted into the stomach and the distal esophagus, as previously described [8, 33]. Balloon catheters were connected to a differential pressure transducer (DPT-100 TM ; UT Medical Products, Athlone, Ireland) and an amplifier (ADInstruments, Oxford, UK) [7, 8, 33]. Pressure data for twPgas, twPes, and twPdi (defined as twPes – twPgas) were continuously displayed using LabChart TM software (ADInstruments, Oxford, UK) [11, 27] (online suppl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twitch esophageal pressure (twPes) and twPgas were simultaneously recorded using balloon catheters (Cooper Surgical, Trumbull, CT, USA) transnasally inserted into the stomach and the distal esophagus, as previously described [8, 33]. Balloon catheters were connected to a differential pressure transducer (DPT-100 TM ; UT Medical Products, Athlone, Ireland) and an amplifier (ADInstruments, Oxford, UK) [7, 8, 33]. Pressure data for twPgas, twPes, and twPdi (defined as twPes – twPgas) were continuously displayed using LabChart TM software (ADInstruments, Oxford, UK) [11, 27] (online suppl.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were also instructed to repeatedly perform a maximum sniff maneuver (a short, sharp inspiratory maneuver). The best of 5 consecutive efforts was used for analysis [7, 8, 33].…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 displays the percentage reduction in CAI from baseline for each patient. The oxygen desaturation index (4%) decreased from a median of 41 [30,56] events per hour to 19 [8,37] in the treatment group and increased from 33 [25,50] events per hour to 39 [26,57] in control (between groups p < .001). Marked or moderate improvement in the patient global assessment quality of life instrument was noted by 60% (35/58) treatment versus 6% (4/72) control subjects (p < .001) and daytime sleepiness decreased 2.5 [− 7, − 1] points in treatment compared with increasing 1.0 [− 2, 2] points in control based on the Epworth Sleepiness Scale (p < .001).…”
Section: Resultsmentioning
confidence: 97%
“…For this approach TPNS may make a difference in addressing the pathophysiology of CSA, including hypoxia, more profoundly than mask-based therapy have the ability to. In this context it has been shown that positive airway pressure therapies have adversely impacted blood pressure and sympathetic nerve activity in heart failure patients [25]. Further investigations on phrenic nerve stimulation and effects on the sympatho-vagal system are needed using direct microneurography to assess physiologic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ventilation due to pressure support from ASV might worsen respiratory alkalosis, with a consequent increase in potassium excretion, thus predisposing to fatal arrhythmia. Although this is not supported by data demonstrating that ASV acutely improves alkalosis 7 and reduces appropriate defi brillator shocks, 19 ASV has been shown to increase alkalosis during wakefulness, 20 and the long-term eff ects of ASV on alkalosis and electrolyte balance in patients whose CSA is chronically suppressed is not clear. Unfavorable hemodynamics in those with pulmonary hypertension and right ventricular dysfunction, device-patient dyssynchrony with increased sleep fragmentation, or adverse eff ects of positive pressure on cardiac remodeling are also possible.…”
mentioning
confidence: 97%